Problems of multifunctional centers of the Russian federation and ways to solve them ("Journal "U". Economy. Management. Finance.", 2023)
Today, multifunctional centers are becoming an essential part of the life of some modern countries, including Russia. The system of interaction between the MFC and public authorities is a process of continuous improvement. However, before improving the interaction process, it is necessary to identify existing problems that need to be addressed. This article discusses the problems of the functioning of the MFC and ways to solve them.
Keywords: multifunctional centers; public services; applicant; one-stop shop principle; documents; MFC portal; personnel